Differential diagnosis of breast tumors on the basis of radiothermometric findings - V. I. Vidyukov; Ch. K. Mustafin; R. A. Kerimov; L. N. Fisher (Опухоли женской репродуктивной системы, 2016)
The paper presents a method for the differential diagnosis of breast tumors in accordance with radiothermometric findings, which is based on the authors’ developed diagnostic technique (Patent No. 2532372 dated 5 September 2014). The radiometric method was used to examine 119 patients with malignant breast tumors, 53 patients with benign breast tumors, and 60 women without breast involvement. The data were obtained in 3 institutions: the Russian Medical Academy of Postgraduate Education, the N.N. Blokhin Russian Cancer Research Center, and Moscow Oncology Dispensary Five. A microwave radiothermometer was used to measure core and skin temperatures in 9 symmetrical points of each breast. Using the findings as a basis, the authors proposed quantitative criteria that ensured that breast tumors should be differentially diagnosed with high specificity.